ANALISIS HUBUNGAN ANTARA KEPERCAYAAN, KOMITMEN DAN KESEDIAAN NASABAH MENGGUNAKAN LAYANAN INTERNET BANKING - , RANDY ARDIANSYAH; , Dr. Sumiyana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted to examines the model of internet banking which involves the concept of trust and commitment to the willingness to try Internet Banking, based on data collected from a survey of Internet Banking users in Jakarta. The sample of this research is 421 users of Internet Banking at Bank Negara Indonesia (BNI). After the establishment of a conceptual model that links trust and commitment to the willingness to try Internet Banking, the empirical findings show that higher levels of trust and commitment are significantly associated with a greater willingness to try Internet Banking. The paper also investigates security, ethics, privacy, openness, speed of response, quality of information, regulatory control, technology advancement, and reputation as determinants of trust. In addition, measurement of customerâs commitment to the willingness to try internet banking was measured using affective commitment and calculative commitment. Data were analyzed with the Structural Equation Model (SEM) using statistical software AMOS 19.0. The results of this research indicated that security, ethics, privacy, openness, quality of information, regulatory control, technology advancement, reputation, affective commitment and calculative commitment are found to be significant determinants. This study concludes with a discussion of the implications of these findings for Internet banks.